Microfluidic systems and devices for molecular capture, manipulation, and analysis - Chou, Chia-Fu (2018)
Methods, systems, and devices are disclosed for molecular capture, manipulation, and analysis. In one aspect, a device to aggregate and characterize particles in a fluid includes an electrically insulative substrate including a channel to carry an electrically conducting fluid containing particles, electrodes located in the channel forming a nanoscale opening and including an insulating layer over their surface at the opening, a first circuit to apply a non-uniform ac electric field and a dc bias signal across the electrodes, in which the applied non-uniform ac electric field produces a positive dielectrophoretic force to aggregate the particles in a trapping region including the opening and adjacent region, a second circuit to detect changes in a dc current caused by at least some of the particles in the trapping region, and an optical device that directs a coherent light beam on the opening to determine Raman spectra of the particles in the trapping region.